The Influence Of Work Motivation And Discipline On Employee Performance With Leadership As Mediation Variables In The Business Cooperative Office Small To Medium Industrial And Government Trade Medan City - Khairunnisa, Khairunnisa; Hermansyur, Hermansyur; Nahrisah, Ezzah (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research aims to determine whether the influence of work motivation, discipline and leadership are mediating variables between motivation and employee performance at the Department of Cooperatives and smes of the Medan Government. The population in this study were all 99 employees who worked in the Department of Cooperatives and SMEs of the Medan Government. The data collection technique used in the research was a questionnaire. Because productive age is considered capable of influencing a person's work effectiveness and creative ideas. The research results show that the variables of motivation and work discipline have a significant influence on performance. The leadership variable which acts as a mediating variable in this study was able to mediate significantly between the variables of motivation and work discipline on performance.